Educator perspectives on stressors and health: a qualitative study of U.S. K-12 educators in February 2022 - Jennifer M. Cavallari; Sierra M. Trudel; Natalie R. Charamut; Adekemi O. Suleiman; Lisa M. H. Sanetti; Megan N. Miskovsky; Matthew E. Brennan; Alicia G. Dugan (BMC, 2024)
Abstract Background Teachers experienced increased stressors and stress during the initial onset of the COVID-19 pandemic. While many educators returned to in-person instruction in the 2021-2022 school year, they faced changing job demands and stressors which has important implications for educator well-being. We sought to understand the stressors and health impacts faced by U.S. educators in the 2021-2022 school year, two years following the acute phase of the pandemic. Methods Thirty-four certified educators based in Connecticut, USA participated in four virtual focus groups in February 2022. A semi-structured focus group script, designed by the research team and guided by the job demands-resources model, was administered to understand stressors and stress impacts. Data were transcribed and analyzed using the constant comparative method to identify themes and sub-themes. Themes were summarized based on how many participants mentioned them. Results Analysis of the qualitative data yielded three themes concerning the well-being impacts of stress: physical health and health behaviors, psychological health, and relationships and social well-being behaviors. The majority of educators indicated impacts in these domains with 76% indicating impacts on physical health and health behaviors (e.g. poor sleep, physical exhaustion, lack of exercise, unhealthy eating), 62% indicating impacts on psychological health (e.g. emotional exhaustion, anxiety, negative self-evaluation); and 68% indicating impacts on relationships social well-being behaviors (e.g. connections with family or friends, connections with others, relationships with coworkers). The majority (94%) of educators indicated that stressors from the school or district with the majority (91%) citing stressors related to protocols/expectations (e.g. excessive or increased demands, insufficient or decreased resources) and some (38%) administrators. Over half (62%) indicated personal stressors including personal/home life (41%), high personal expectations (18%), and income (18%). Some (35%) indicated either the pandemic (26%) or safety concerns (9%) were stressors. Some (24%) cited students' parents as a stressor and a few indicated community (12%), students (12%), and state or national level (9%) stressors. Conclusion Educator well-being continued to be impacted in the post-pandemic era. Targeted interventions are needed to reduce school and district-related demands and to address stress-related educator well-being.